Optimalaisasi Penerimaan Pajak Kendaraan Bermotor Pada Upt Pengelolaan Pendapatan Panam Tahun 2022 - 2023 - Haryadi, Haryadi (Jurnal Kajian Pemerintah: Journal of Government, Social and Politics, 2024)
This study aims to look at the optimization of motor vehicle tax revenue at the Panam Revenue Management Unit, Riau Province Regional Revenue Agency in 2022 - 2023. There is a decrease in motor vehicle tax revenue that occurred in the Panam Revenue Management Unit in 2022 - 2023. Therefore, it is necessary to take strategic steps to increase local revenue. This research uses descriptive qualitative methods, utilizing literature sources and available documents as analytical materials. This research found that the Riau Province Regional Revenue Agency has utilized technology in vehicle tax collection with an online system. In addition, several programs have also been created to make it easier for people to pay taxes such as driv thru and other tax relief programs. Strategies that can be applied, such as digitizing payment systems, data integration between agencies, and socialization and education to increase taxpayer awareness. The application of incentives in the form of tax deductions and fines for non-compliance, as well as strict supervision through raids and modern technology, were identified as effective measures. Cooperation with third parties and simplification of administrative procedures can also simplify the payment process. In addition, rewarding compliant taxpayers and periodic review of tax rates are necessary to maintain fairness and relevance of rates. The implementation of these strategies is expected to significantly increase motor vehicle tax revenue, support regional development, and improve the quality of public services.